A kind of bending-resistant stainless steel belt and its preparation process
Stainless steel strips are prepared through hot rolling, annealing, pickling, cold rolling, solid solution treatment and magnetic field-assisted laser cladding processes, and coated with anti-corrosion coatings, which solves the poor bending resistance, complex preparation process and corrosion resistance of traditional stainless steel strips. The problem of insufficient results has achieved efficient bending resistance and corrosion resistance.
Patent Information
- Application Number
- CN202411311695.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-20
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2044-09-20
AI Technical Summary
Traditional stainless steel belts are prone to deform or break when bent, the preparation process is complex and costly, and the surface finish and corrosion resistance are insufficient.
Stainless steel strips are prepared by hot rolling, annealing, pickling, cold rolling, and solid solution treatment, and a magnetic field-assisted laser cladding process is used to prepare the cladding layer, and finally coat anti-corrosion coating to form a bending-resistant stainless steel strip.
It improves the bending resistance, plasticity and corrosion resistance of stainless steel belts, extends service life, and reduces production costs.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of stainless steel strips, in particular to a bending-resistant stainless steel strip and a preparation process thereof. Background Art
[0002] With the development of modern industry, the demand for stainless steel strips with excellent bending resistance is increasing. As an important structural material, stainless steel strips are widely used in aerospace, automobile manufacturing, construction and other fields. However, traditional stainless steel strips are often prone to deformation or breakage when subjected to bending forces, which affects their service life and performance.
[0003] The existing technology has the following problems: 1. The bending resistance of traditional stainless steel strips is poor, and they are prone to plastic deformation or fracture; 2. The preparation process is complicated, the cost is high, and the production efficiency is low; 3. The surface finish and corrosion resistance of traditional stainless steel strips need to be improved.
[0004] Therefore, we propose a bending-resistant stainless steel strip and a preparation process thereof. Summary of the invention
[0005] The object of the present invention is to provide a bending-resistant stainless steel strip and a preparation process thereof, so as to solve the problems raised in the above-mentioned background technology.
[0006] In order to solve the above technical problems, the present invention provides the following technical solutions:
[0007] A process for preparing a bending-resistant stainless steel strip comprises the following steps:
[0008] Step S1: hot rolling, annealing, pickling, cold rolling and solution treatment of the stainless steel billet to obtain a stainless steel strip;
[0009] Step S2: After grinding, polishing, cleaning and drying the stainless steel strip in sequence, a cladding coating is coated on its surface, preheating is performed, and then a cladding layer is prepared by a magnetic field-assisted laser cladding process, and tempering is performed to obtain a pretreated stainless steel strip;
[0010] Step S3: coating the surface of the pretreated stainless steel strip with an anti-corrosion coating, and after drying and curing, forming an anti-corrosion coating to obtain a bending-resistant stainless steel strip.
[0011] Furthermore, in step S1, the stainless steel billet includes the following elements in weight percentage: C: 0.02-0.05%, Cr: 14-16%, Si: 0.2-0.6%, Mn: 0.60-1.00%, Ni: 3.2-5.4%, B: 0.001-0.007%, V: 0.10-0.30%, Mo: 1.0-2.5%, Ti: 0.05-0.10%, Zr: 0.02-0.05%, Y: 0.02-0.05%, N: 0.03-0.08%, S≤0.005%, P≤0.004%, and the balance is Fe.
[0012] Furthermore, in step S1, the stainless steel billet is prepared in sequence through converter smelting, VOD refining, LF refining, and slab continuous casting.
[0013] Furthermore, in step S1, the hot rolling temperature is 900-1150°C.
[0014] Furthermore, in step S1, the annealing process conditions are: keeping at 820-900°C for 1-2h, slowly cooling to 300-400°C after keeping, and then air cooling to room temperature.
[0015] Furthermore, in step S1, the process conditions of the solution treatment are: keeping at 900-950° C. for 1-2 hours, followed by water cooling.
[0016] Furthermore, in step S1, the thickness of the stainless steel strip is 1-5 mm.
[0017] Furthermore, in step S2, the preparation method of the cladding coating is as follows:
[0018] The iron-based self-fluxing alloy powder, titanium iron powder and molybdenum-lanthanum alloy powder are ball-milled to obtain a mixed powder; the mixed powder, cellulose acetate and acetone are evenly mixed to obtain a cladding coating.
[0019] Furthermore, the ball milling time is 8-12 hours, and the ball milling speed is 150-200 r / min.
[0020] Furthermore, the cladding coating comprises the following components by weight: 20-40 parts of iron-based self-fluxing alloy powder, 1-3 parts of ferrotitanium powder, 1-2 parts of molybdenum-lanthanum alloy powder, 0.1-0.3 parts of cellulose acetate, and 5-10 parts of acetone.
[0021] Furthermore, in step S2, the preheating temperature is 100-200°C.
[0022] Furthermore, in step S2, the process conditions of magnetic field-assisted laser cladding are: laser power 1000-1500 W, scanning speed 5-10 mm / s, spot diameter 2-5 mm, argon gas flow rate 15-18 L / min, and magnetic field strength 10-30 T.
[0023] Furthermore, in step S2, the tempering process conditions are: first keep warm at 400-440°C for 1-2 hours, then keep warm at 460-500°C for 3-4 hours, and air cool.
[0024] Furthermore, in step S2, the thickness of the cladding layer is 0.5-3.0 mm.
[0025] Furthermore, in step S3, the preparation method of the anti-corrosion coating is as follows:
[0026] Step (1): adjusting the pH of Tris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a dopamine hydrochloride solution, then adding graphene oxide and mixing, ultrasonically treating for 1-2 hours, stirring for 20-24 hours, washing, centrifuging, and drying to obtain modified graphene oxide;
[0027] Step (2): Mix tannic acid and deionized water evenly, add 4-formylphenylboronic acid and mix evenly to obtain compound A; mix boron nitride and sodium hydroxide solution, ultrasonically treat for 2-3 hours, stir for 5-7 hours, react at 125-135°C for 46-48 hours, filter, wash and dry to obtain hydroxylated boron nitride; mix hydroxylated boron nitride and toluene evenly, add 4,4′-diphenylmethane diisocyanate and dibutyltin dilaurate and mix evenly, heat to 75-85°C under nitrogen protection, react for 8-10 hours, filter, wash and dry to obtain isocyanate boron nitride; mix isocyanate boron nitride, compound A and dibutyltin dilaurate evenly, heat to 75-85°C under nitrogen protection, react for 8-10 hours, filter, wash and dry to obtain formaldehyde boron nitride;
[0028] Step (3): under nitrogen protection, the aminophenyl POSS, modified graphene oxide and formaldehyde-modified boron nitride are mixed evenly, acetic acid is added, and the mixture is reacted at 75-85° C. for 4-6 hours. After filtering, washing and drying, an anticorrosive composite is obtained;
[0029] Step (4): Evenly mix the epoxy resin and xylene, add aluminum dihydrogen phosphate, anti-corrosion compound, curing agent, leveling agent and defoaming agent, and mix evenly to obtain an anti-corrosion coating.
[0030] In the above technical scheme, dopamine is coated on the surface of graphene oxide by self-polymerization advantage, so that the surface of graphene oxide has abundant carbonyl groups to obtain modified graphene oxide; aldehyde groups are introduced by reacting tannic acid and 4-formylphenylboronic acid to obtain compound A containing borate ester bonds, and then the remaining hydroxyl groups in compound A are reacted with isocyanate-treated boron nitride to obtain formaldehyde-treated boron nitride; finally, the amino groups on the aminophenyl POSS and modified graphene oxide and formaldehyde-treated boron nitride undergo Schiff base reaction to obtain an anti-corrosion composite, thereby achieving an effective combination of aminophenyl POSS, graphene oxide and boron nitride, and having excellent anti-corrosion performance and stability.
[0031] Furthermore, in step (1), the concentration of the Tris-HCl buffer is 0.01 mol / L, the concentration of the dopamine hydrochloride solution is 3-5 g / L, and the mass of the graphene oxide is 0.2-0.5% of the mass of the Tris-HCl buffer.
[0032] Furthermore, in step (2), the mass ratio of tannic acid, deionized water and 4-formylphenylboric acid is 1:(15-20):(0.2-0.4).
[0033] Furthermore, in step (2), the mass ratio of boron nitride to sodium hydroxide solution is 1:(150-200), the concentration of sodium hydroxide solution is 2-4 mol / L, and the mass ratio of hydroxylated boron nitride, toluene, 4, 4′-diphenylmethane diisocyanate and dibutyltin dilaurate is 1:(100-120):(10-12):(0.03-0.05).
[0034] Furthermore, in the step (2), the mass ratio of isocyanate boron nitride, compound A and dibutyltin dilaurate is 1:(1-2):(0.03-0.05).
[0035] Furthermore, in the step (3), the mass ratio of aminophenyl POSS, modified graphene oxide and formaldehyded boron nitride is 1:(0.5-1.5):(1-2), and the amount of acetic acid used is 1-3% of the mass of aminophenyl POSS.
[0036] Furthermore, the anti-corrosion coating comprises the following components by weight: 50-60 parts of epoxy resin, 25-35 parts of xylene, 5-10 parts of aluminum dihydrogen phosphate, 10-15 parts of anti-corrosion compound, 5-10 parts of curing agent, 0.1-0.3 parts of leveling agent, and 0.1-0.2 parts of defoaming agent.
[0037] Furthermore, the curing agent is a polyamide curing agent.
[0038] Furthermore, in step S3, the coating process conditions are: spraying, spraying pressure 4-6MPa, spraying distance 230-250mm, and moving speed 5-10m / min.
[0039] Furthermore, the thickness of the anti-corrosion coating is 100-150 μm.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. The present invention provides a bending-resistant stainless steel strip and its preparation process. By precisely controlling the content and ratio of various elements in the stainless steel strip, the bending strength and plasticity of the material can be improved while ensuring that the material has high strength, thereby making the stainless steel strip have better bending resistance. Adding the Mo element can hinder the aggregation of carbonitrides at the grain boundaries, reduce the brittle phases at the grain boundaries, and improve the plasticity and tensile strength of the material; adding the Ti element can form stable carbides, improve the strength and hardness of the material, and also refine the grains, improve the texture and plasticity of the material; adding the Y element can improve the high-temperature strength and heat resistance of the material, and also improve the grain refinement effect of the material, and enhance the material's antioxidant and corrosion resistance.
[0042] 2. The present invention provides a bending-resistant stainless steel belt and its preparation process. By using iron-based self-fluxing alloy powder, titanium iron powder and molybdenum-lanthanum alloy powder as cladding materials and cellulose acetate as a binder, a magnetic field-assisted laser cladding process is used to prepare a cladding layer on the surface of the stainless steel belt. The cladding layer has high hardness and wear resistance, can effectively enhance the bending resistance of the stainless steel belt, and reduce the risk of deformation and breakage; and a tempering treatment is performed to eliminate the residual stress generated in the cladding layer, improve the stability of the internal structure and performance of the stainless steel belt, and further improve the toughness of the stainless steel belt.
[0043] 3. A bending-resistant stainless steel strip and its preparation process of the present invention utilize dopamine to be coated on the surface of graphene oxide through self-polymerization advantage, so that the surface of graphene oxide has abundant carbonyl groups to obtain modified graphene oxide; tannic acid and 4-formylphenylboronic acid are reacted to introduce aldehyde groups to obtain compound A containing borate ester bonds, and then the remaining hydroxyl groups in compound A are reacted with isocyanate-treated boron nitride to obtain formaldehyde-treated boron nitride; finally, the amino groups on the aminophenyl POSS and the modified graphene oxide and formaldehyde-treated boron nitride undergo Schiff base reaction to obtain an anti-corrosion composite, thereby achieving an effective combination of aminophenyl POSS, graphene oxide and boron nitride, and having excellent anti-corrosion performance and stability; epoxy resin, anti-corrosion composite, aluminum dihydrogen phosphate and a variety of additives are uniformly mixed to obtain an anti-corrosion coating, which can effectively protect the stainless steel strip and extend its service life. DETAILED DESCRIPTION
[0044] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0045] In this embodiment, the iron-based self-fluxing alloy powder: model Fe50, 45μm; titanium iron powder: brand FeTi40-A, 80-100 mesh, sourced from Nangong Jingxing Alloy Welding Material Co., Ltd.; molybdenum-lanthanum alloy powder: La2O3 content is 0.5-5.0%, item number TLS2023, sourced from Beijing Siyalongling Science and Technology Trade Co., Ltd.; cellulose acetate: cellulose acetate butyrate, item number 551-0.2, sourced from Dongguan Guangtai Plastic Raw Materials Co., Ltd. ; Graphene oxide: thickness 1-3nm, diameter 4-7μm, number of layers 2-5, sourced from Zhejiang Zhiti Nano Micro New Materials Co., Ltd.; Boron nitride: hexagonal boron nitride, particle size 20-45μm; Aluminum dihydrogen phosphate: CAS No. 13530-50-2; Epoxy resin: epoxy resin E51, epoxy equivalent 184-194g / ep; Leveling agent: Keying KYC-615; Defoaming agent: model BYK-028; Curing agent: polyamide 650.
[0046] In the following examples and comparative examples, 1 part is equal to 10 g.
[0047] Embodiment 1: A process for preparing a bending-resistant stainless steel strip, comprising the following processes:
[0048] Step S1: hot rolling (hot rolling temperature is 900°C), annealing (keeping at 820°C for 1 hour, slowly cooling to 300°C after keeping, and then air cooling to room temperature), pickling, cold rolling, and solution treatment (keeping at 900°C for 1 hour, followed by water cooling) of the stainless steel billet to obtain a stainless steel strip;
[0049] Step S2: ball milling 20 parts of iron-based self-fluxing alloy powder, 1 part of titanium iron powder and 1 part of molybdenum-lanthanum alloy powder (ball milling time is 8 hours, ball milling speed is 150r / min) to obtain a mixed powder; the mixed powder, 0.1 parts of cellulose acetate and 5 parts of acetone are evenly mixed to obtain a cladding coating; the stainless steel strip is grinded, polished, cleaned and dried in sequence, and then the cladding coating is coated on its surface, and preheated (preheating temperature is 100°C), and then a 0.5mm cladding layer is prepared by a magnetic field-assisted laser cladding process (laser power 1000W, scanning speed 5mm / s, spot diameter 2mm, argon flow rate 15L / min, magnetic field strength 10T), and tempering is performed (first at 400°C for 1h, then at 460°C for 3h, and air-cooled) to obtain a pretreated stainless steel strip;
[0050] Step S3: coating the surface of the pretreated stainless steel strip with an anti-corrosion coating (by spraying, with a spraying pressure of 4 MPa, a spraying distance of 230 mm, and a moving speed of 5 m / min), and after drying and curing, forming an anti-corrosion coating of 100 μm to obtain a bending-resistant stainless steel strip;
[0051] The stainless steel billet includes the following elements in weight percentage: C: 0.02%, Cr: 14%, Si: 0.2%, Mn: 0.60%, Ni: 3.2%, B: 0.001%, V: 0.10%, Mo: 1.0%, Ti: 0.05%, Zr: 0.02%, Y: 0.02%, N: 0.03%, S≤0.005%, P≤0.004%, and the balance is Fe;
[0052] In step S3, the preparation method of the anti-corrosion coating is as follows:
[0053] Step (1): adjusting 1000 parts of 0.01 mol / L Tris-HCl buffer to pH 8.5, adding dopamine hydrochloride and mixing evenly to obtain a 3 g / L dopamine hydrochloride solution, then adding 2 parts of graphene oxide and mixing, ultrasonically treating for 1 hour, stirring for 20 hours, washing, centrifuging, and drying to obtain modified graphene oxide;
[0054] Step (2): 4 parts of tannic acid and 60 parts of deionized water are mixed evenly, and 0.8 parts of 4-formylphenylboric acid are added and mixed evenly to obtain compound A; 4 parts of boron nitride and 600 parts of 2 mol / L sodium hydroxide solution are mixed, ultrasonically treated for 2 hours, stirred for 5 hours, reacted at 125°C for 46 hours, filtered, washed, and dried to obtain hydroxylated boron nitride; 4 parts of hydroxylated boron nitride and 400 parts of toluene are mixed evenly, and 40 parts of 4, 4′-diphenylmethane diisocyanate and 0.12 parts of dibutyltin dilaurate were mixed evenly, heated to 75°C under nitrogen protection, reacted for 8 hours, filtered, washed, and dried to obtain isocyanate boron nitride; 4 parts of isocyanate boron nitride, 4 parts of compound A and 0.12 parts of dibutyltin dilaurate were mixed evenly, heated to 75°C under nitrogen protection, reacted for 8 hours, filtered, washed, and dried to obtain formaldehyde boron nitride;
[0055] Step (3): Under nitrogen protection, 4 parts of aminophenyl POSS, 2 parts of modified graphene oxide and 4 parts of formaldehyded boron nitride are mixed evenly, 0.04 parts of acetic acid are added, and the mixture is reacted at 75° C. for 4 hours. After filtering, washing and drying, an anticorrosive composite is obtained;
[0056] Step (4): 50 parts of epoxy resin and 25 parts of xylene are mixed evenly, and 5 parts of aluminum dihydrogen phosphate, 10 parts of anticorrosive compound, 5 parts of curing agent, 0.1 parts of leveling agent and 0.1 parts of defoaming agent are added and mixed evenly to obtain an anticorrosive coating.
[0057] Embodiment 2: A process for preparing a bending-resistant stainless steel strip, comprising the following processes:
[0058] Step S1: hot rolling (hot rolling temperature is 1000°C), annealing (keeping at 850°C for 1.5 hours, slowly cooling to 350°C after keeping, and then air cooling to room temperature), pickling, cold rolling, and solution treatment (keeping at 920°C for 1.5 hours, followed by water cooling) of the stainless steel billet to obtain a stainless steel strip;
[0059] Step S2: 30 parts of iron-based self-fluxing alloy powder, 2 parts of titanium iron powder and 1.5 parts of molybdenum-lanthanum alloy powder are ball-milled (ball milling time is 10 hours, ball milling speed is 180r / min) to obtain a mixed powder; the mixed powder, 0.2 parts of cellulose acetate and 8 parts of acetone are evenly mixed to obtain a cladding coating; the stainless steel strip is grinded, polished, cleaned and dried in sequence, and then the cladding coating is coated on its surface, and preheated (preheating temperature is 150°C), and then a 1mm cladding layer is prepared by a magnetic field-assisted laser cladding process (laser power 1200W, scanning speed 8mm / s, spot diameter 4mm, argon flow rate 16L / min, magnetic field strength 20T), and tempered (first at 420°C for 1.5 hours, then at 480°C for 3.5 hours, air-cooled) to obtain a pretreated stainless steel strip;
[0060] Step S3: coating the surface of the pretreated stainless steel strip with an anti-corrosion coating (by spraying, with a spraying pressure of 5 MPa, a spraying distance of 240 mm, and a moving speed of 9 m / min) to form an anti-corrosion coating of 120 μm, thereby obtaining a bending-resistant stainless steel strip;
[0061] The stainless steel billet includes the following elements in weight percentage: C: 0.03%, Cr: 15%, Si: 0.4%, Mn: 0.8%, Ni: 4.2%, B: 0.005%, V: 0.2%, Mo: 2%, Ti: 0.08%, Zr: 0.04%, Y: 0.04%, N: 0.05%, S≤0.005%, P≤0.004%, and the balance is Fe;
[0062] In step S3, the preparation method of the anti-corrosion coating is as follows:
[0063] Step (1): adjusting 800 parts of 0.01 mol / L Tris-HCl buffer to pH 8.5, adding dopamine hydrochloride and mixing evenly to obtain a 4 g / L dopamine hydrochloride solution, then adding 4 parts of graphene oxide and mixing, ultrasonically treating for 1.5 h, stirring for 22 h, washing, centrifuging, and drying to obtain modified graphene oxide;
[0064] Step (2): 9 parts of tannic acid and 150 parts of deionized water are mixed evenly, and 2.7 parts of 4-formylphenylboronic acid are added and mixed evenly to obtain compound A; 6 parts of boron nitride and 1000 parts of 3 mol / L sodium hydroxide solution are mixed, ultrasonically treated for 2.5 hours, stirred for 6 hours, reacted at 130°C for 47 hours, filtered, washed, and dried to obtain hydroxylated boron nitride; 6 parts of hydroxylated boron nitride and 660 parts of toluene are mixed evenly, and 66 parts of 4, 4′-diphenylmethane diisocyanate and 0.24 parts of dibutyltin dilaurate were mixed evenly, heated to 80°C under nitrogen protection, reacted for 9 hours, filtered, washed, and dried to obtain isocyanate boron nitride; 6 parts of isocyanate boron nitride, 9 parts of compound A and 0.24 parts of dibutyltin dilaurate were mixed evenly, heated to 80°C under nitrogen protection, reacted for 9 hours, filtered, washed, and dried to obtain formaldehyde boron nitride;
[0065] Step (3): Under nitrogen protection, 4 parts of aminophenyl POSS, 4 parts of modified graphene oxide and 6 parts of formaldehyded boron nitride are mixed evenly, 0.08 parts of acetic acid are added, and the mixture is reacted at 80° C. for 5 h. After filtering, washing and drying, an anticorrosive composite is obtained;
[0066] Step (4): 55 parts of epoxy resin and 30 parts of xylene are mixed evenly, and 8 parts of aluminum dihydrogen phosphate, 12 parts of anti-corrosion compound, 8 parts of curing agent, 0.2 parts of leveling agent and 0.15 parts of defoaming agent are added and mixed evenly to obtain an anti-corrosion coating.
[0067] Embodiment 3: A process for preparing a bending-resistant stainless steel strip, comprising the following processes:
[0068] Step S1: hot rolling (hot rolling temperature is 1150°C), annealing (keeping at 900°C for 2h, slowly cooling to 400°C after keeping, and then air cooling to room temperature), pickling, cold rolling, and solution treatment (keeping at 950°C for 2h, followed by water cooling) of the stainless steel billet to obtain a stainless steel strip;
[0069] Step S2: 40 parts of iron-based self-fluxing alloy powder, 3 parts of titanium iron powder and 2 parts of molybdenum-lanthanum alloy powder are ball-milled (ball milling time is 12 hours, ball milling speed is 200r / min) to obtain a mixed powder; the mixed powder, 0.3 parts of cellulose acetate and 10 parts of acetone are mixed evenly to obtain a cladding coating; the stainless steel strip is grinded, polished, cleaned and dried in sequence, and then the cladding coating is coated on its surface, and preheated (preheating temperature is 200°C), and then a 5mm cladding layer is prepared by a magnetic field-assisted laser cladding process (laser power 1500W, scanning speed 10mm / s, spot diameter 5mm, argon flow rate 18L / min, magnetic field strength 30T), and tempered (first at 440°C for 2 hours, then at 500°C for 4 hours, air-cooled) to obtain a pretreated stainless steel strip;
[0070] Step S3: coating the surface of the pretreated stainless steel strip with an anti-corrosion coating (by spraying, with a spraying pressure of 6 MPa, a spraying distance of 250 mm, and a moving speed of 10 m / min) to form an anti-corrosion coating of 150 μm, thereby obtaining a bending-resistant stainless steel strip;
[0071] The stainless steel billet includes the following elements in weight percentage: C: 0.05%, Cr: 16%, Si: 0.6%, Mn: 1.00%, Ni: 5.4%, B: 0.007%, V: 0.30%, Mo: 2.5%, Ti: 0.10%, Zr: 0.05%, Y: 0.05%, N: 0.08%, S≤0.005%, P≤0.004%, and the balance is Fe;
[0072] In step S3, the preparation method of the anti-corrosion coating is as follows:
[0073] Step (1): adjusting 1200 parts of 0.01 mol / L Tris-HCl buffer to pH=8.5, adding dopamine hydrochloride and mixing evenly to obtain a 5 g / L dopamine hydrochloride solution, then adding 6 parts of graphene oxide and mixing, ultrasonically treating for 2 h, stirring for 24 h, washing, centrifuging, and drying to obtain modified graphene oxide;
[0074] Step (2): 16 parts of tannic acid and 320 parts of deionized water are mixed evenly, and 6.4 parts of 4-formylphenylboric acid are added and mixed evenly to obtain compound A; 8 parts of boron nitride and 1600 parts of 4 mol / L sodium hydroxide solution are mixed, ultrasonically treated for 3 hours, stirred for 7 hours, reacted at 135°C for 48 hours, filtered, washed, and dried to obtain hydroxylated boron nitride; 8 parts of hydroxylated boron nitride and 960 parts of toluene are mixed evenly, and 96 parts of 4, 4′-diphenylmethane diisocyanate and 0.4 parts of dibutyltin dilaurate are mixed evenly, heated to 85°C under nitrogen protection, reacted for 10 hours, filtered, washed, and dried to obtain isocyanate boron nitride; 8 parts of isocyanate boron nitride, 16 parts of compound A and 0.4 parts of dibutyltin dilaurate are mixed evenly, heated to 85°C under nitrogen protection, reacted for 10 hours, filtered, washed, and dried to obtain formaldehyde boron nitride;
[0075] Step (3): Under nitrogen protection, 4 parts of aminophenyl POSS, 6 parts of modified graphene oxide and 8 parts of formaldehyded boron nitride are mixed evenly, 0.12 parts of acetic acid are added, and the mixture is reacted at 85° C. for 6 hours. After filtering, washing and drying, an anticorrosive composite is obtained;
[0076] Step (4): 60 parts of epoxy resin and 35 parts of xylene are mixed evenly, and 10 parts of aluminum dihydrogen phosphate, 15 parts of anti-corrosion compound, 10 parts of curing agent, 0.3 parts of leveling agent and 0.2 parts of defoaming agent are added and mixed evenly to obtain an anti-corrosion coating.
[0077] Comparative Example 1: The stainless steel billet includes the following elements in weight percentage: C: 0.1%, Cr: 20%, Si: 1%, Mn: 1%, Ni: 6%, B: 0.01%, V: 0.5%, Mo: 3%, Ti: 0.01%, Zr: 0.01%, Y: 0.01%, N: 0.02%, S≤0.005%, P≤0.004%, and the balance is Fe. The other steps and processes are the same as those in Example 1.
[0078] Comparative Example 2: A process for preparing a bending-resistant stainless steel strip, comprising the following processes:
[0079] Compared with Example 2, in step S2 of Comparative Example 2, the tempering temperature is 600° C., and the other steps are the same as those of Example 2.
[0080] Comparative Example 3: A process for preparing a bending-resistant stainless steel strip, comprising the following processes:
[0081] Compared with Example 2, in Comparative Example 3, the anti-corrosion compound is replaced with graphene oxide of the same mass, and the other steps are the same as those of Example 2.
[0082] Comparative Example 4: A process for preparing a bending-resistant stainless steel strip, comprising the following processes:
[0083] In step S3, the preparation method of the anti-corrosion coating is as follows:
[0084] Step (1): adjusting 800 parts of 0.01 mol / L Tris-HCl buffer to pH 8.5, adding dopamine hydrochloride and mixing evenly to obtain a 4 g / L dopamine hydrochloride solution, then adding 4 parts of graphene oxide and mixing, ultrasonically treating for 1.5 h, stirring for 22 h, washing, centrifuging, and drying to obtain modified graphene oxide;
[0085] Step (2): 9 parts of tannic acid and 150 parts of deionized water are mixed evenly, and 2.7 parts of 4-formylphenylboronic acid are added and mixed evenly to obtain compound A; 6 parts of boron nitride and 1000 parts of 3 mol / L sodium hydroxide solution are mixed, ultrasonically treated for 2.5 hours, stirred for 6 hours, reacted at 130°C for 47 hours, filtered, washed, and dried to obtain hydroxylated boron nitride; 6 parts of hydroxylated boron nitride and 660 parts of toluene are mixed evenly, and 66 parts of 4, 4′-diphenylmethane diisocyanate and 0.24 parts of dibutyltin dilaurate were mixed evenly, heated to 80°C under nitrogen protection, reacted for 9 hours, filtered, washed, and dried to obtain isocyanate boron nitride; 6 parts of isocyanate boron nitride, 9 parts of compound A and 0.24 parts of dibutyltin dilaurate were mixed evenly, heated to 80°C under nitrogen protection, reacted for 9 hours, filtered, washed, and dried to obtain formaldehyde boron nitride;
[0086] Step (3): Under nitrogen protection, 4 parts of aminophenyl POSS, 12 parts of modified graphene oxide and 12 parts of formaldehyded boron nitride are mixed evenly, 0.08 parts of acetic acid are added, and the mixture is reacted at 80° C. for 5 h. After filtering, washing and drying, an anticorrosive composite is obtained;
[0087] Step (4): 55 parts of epoxy resin and 30 parts of xylene are mixed evenly, and 8 parts of aluminum dihydrogen phosphate, 12 parts of anticorrosive compound, 8 parts of curing agent, 0.2 parts of leveling agent and 0.15 parts of defoaming agent are added and mixed evenly to obtain an anticorrosive coating;
[0088] Compared with Example 2, the mass ratio of aminophenyl POSS, modified graphene oxide and formaldehyded boron nitride in Comparative Example 4 is 1:3:3; the other steps are the same as in Example 2.
[0089] Experiment: Take the anti-bending stainless steel strips obtained in Examples 1-3 and Comparative Examples 1-4, prepare samples with a thickness of 3.5 mm, test their properties respectively and record the test results:
[0090] According to the standard GB / T 228.1-2021 "Tensile tests on metallic materials - Part 1: Test methods at room temperature", the tensile strength and yield strength were determined using an electronic universal testing machine with a tensile speed of 1 mm / min. The corrosion resistance was determined according to GB / T 1771-2007 "Determination of resistance of paints and varnishes to neutral salt spray". The experimental steps were as follows: the temperature in the salt spray chamber was 35°C, the test solution was a 5% NaCl solution by mass, and the exposure time was 1000 h.
[0091] Test Results
[0092]
[0093] According to the data in the above table, we can clearly draw the following conclusions:
[0094] 1. Compared with Examples 1-3, the tensile strength and yield strength of the product obtained in Comparative Example 1 are both reduced, indicating that the performance of the stainless steel strip prepared by the present invention is affected by its component ratio. By selecting the component ratio within the range, a material with excellent strength can be prepared.
[0095] 2. Compared with Examples 1-3, the tensile strength and yield strength of the product obtained in Comparative Example 2 are both reduced, which indicates that the tempering temperature set by the present invention can further improve the performance of the stainless steel strip.
[0096] 3. Compared with Examples 1-3, the corrosion resistance of the products obtained in Examples 3 and 4 is reduced. It can be seen that compared with graphene oxide, the anti-corrosion composite prepared by the present invention has better corrosion resistance; at the same time, the performance of the anti-corrosion coating prepared by the present invention is affected by the ratio of each reagent in its preparation process. By selecting a mass ratio within the said range, the prepared coating has excellent corrosion resistance, thereby extending the service life of the stainless steel strip.
[0097] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variations thereof are intended to cover non-exclusive inclusion, so that a process method article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process method article or device.
[0098] Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A process for preparing a bending-resistant stainless steel strip, characterized in that: The steps include: Step S1: hot rolling, annealing, pickling, cold rolling and solution treatment of the stainless steel billet to obtain a stainless steel strip; Step S2: After grinding, polishing, cleaning and drying the stainless steel strip in sequence, a cladding coating is coated on its surface, preheating is performed, and then a cladding layer is prepared by a magnetic field-assisted laser cladding process, and tempering is performed to obtain a pretreated stainless steel strip; Step S3: coating the surface of the pretreated stainless steel strip with an anti-corrosion coating, and after drying and curing, forming an anti-corrosion coating to obtain a bending-resistant stainless steel strip; In the step S1, the stainless steel billet includes the following elements in weight percentage: C: 0.02-0.05%, Cr: 14-16%, Si: 0.2-0.6%, Mn: 0.60-1.00%, Ni: 3.2-5.4%, B: 0.001-0.007%, V: 0.10-0.30%, Mo: 1.0-2.5%, Ti: 0.05-0.10%, Zr: 0.02-0.05%, Y: 0.02-0.05%, N: 0.03-0.08%, S≤0.005%, P≤0.004%, and the balance is Fe; The cladding coating comprises the following components by weight: 20-40 parts of iron-based self-fluxing alloy powder, 1-3 parts of ferro-titanium powder, 1-2 parts of molybdenum-lanthanum alloy powder, 0.1-0.3 parts of cellulose acetate, and 5-10 parts of acetone; In step S2, the tempering process conditions are: first, keep at 400-440°C for 1-2 hours, then keep at 460-500°C for 3-4 hours, and air cool; In step S3, the preparation method of the anti-corrosion coating is as follows: Step (1): adjusting the pH of Tris-HCl buffer to 8.5, adding dopamine hydrochloride and mixing evenly to obtain a dopamine hydrochloride solution, then adding graphene oxide and mixing, ultrasonically treating for 1-2 hours, stirring for 20-24 hours, washing, centrifuging, and drying to obtain modified graphene oxide; Step (2): Mix tannic acid and deionized water evenly, add 4-formylphenylboronic acid and mix evenly to obtain compound A; mix boron nitride and sodium hydroxide solution, ultrasonically treat for 2-3 hours, stir for 5-7 hours, react at 125-135°C for 46-48 hours, filter, wash and dry to obtain hydroxylated boron nitride; mix hydroxylated boron nitride and toluene evenly, add 4, 4′-diphenylmethane diisocyanate and dibutyltin dilaurate and mix evenly, heat to 75-85°C under nitrogen protection, react for 8-10 hours, filter, wash and dry to obtain isocyanate boron nitride; mix isocyanate boron nitride, compound A and dibutyltin dilaurate evenly, heat to 75-85°C under nitrogen protection, react for 8-10 hours, filter, wash and dry to obtain formaldehyde boron nitride; Step (3): under nitrogen protection, the aminophenyl POSS, modified graphene oxide and formaldehyde-modified boron nitride are mixed evenly, acetic acid is added, and the mixture is reacted at 75-85° C. for 4-6 hours. After filtering, washing and drying, an anticorrosive composite is obtained; Step (4): mixing the water-based epoxy resin and xylene evenly, adding aluminum dihydrogen phosphate, anti-corrosion compound, curing agent, leveling agent and defoaming agent and mixing evenly to obtain an anti-corrosion coating; In the step (3), the mass ratio of aminophenyl POSS, modified graphene oxide and formaldehyded boron nitride is 1: (0.5-1.5): (1-2); The anticorrosive coating comprises the following components by weight: 50-60 parts of epoxy resin, 25-35 parts of xylene, 5-10 parts of aluminum dihydrogen phosphate, 10-15 parts of anticorrosive compound, 5-10 parts of curing agent, 0.1-0.3 parts of leveling agent and 0.1-0.2 parts of defoaming agent.
2. The process for preparing a bending-resistant stainless steel strip according to claim 1, characterized in that: In step S2, the preparation method of the cladding coating is as follows: The iron-based self-fluxing alloy powder, titanium iron powder and molybdenum-lanthanum alloy powder are ball-milled to obtain a mixed powder; the mixed powder, cellulose acetate and acetone are evenly mixed to obtain a cladding coating.
3. The process for preparing a bending-resistant stainless steel strip according to claim 1, characterized in that: In step S2, the process conditions of magnetic field-assisted laser cladding are: laser power 1000-1500 W, scanning speed 5-10 mm / s, spot diameter 2-5 mm, argon gas flow rate 15-18 L / min, and magnetic field strength 10-30 T.
4. A bending-resistant stainless steel strip obtained by the preparation process according to any one of claims 1 to 3.
Citation Information
Patent Citations
Organosilicone modified epoxy resin high-temperature-resistant anti-corrosion coating and preparation method thereof
CN106634409A
High-thermal-conductivity graphene heat dissipation film and preparation method thereof
CN112608565A